Hand Gesture Detection Implemented based on Long Short-Term Memory (LSTM) Method - I Gede Wiryawan; Taufiq Rizaldi; Pramuditha Shinta Dewi Puspitasari; Arvita Agus Kurniasari (Jurnal Sistem Cerdas, 2025)
The Indonesian government encourages accessibility of information that is friendly to people with disabilities, one of which is through the development of information and communication technology. Efforts to increase accessibility of information and encourage independence of people with disabilities need to be supported by the right solutions. According to the Central Statistics Agency, there were 0.68% of the total population of Indonesia in 2019, this data shows that deafness is one of the highest disabilities in Indonesia. Efforts to increase accessibility of information and encourage independence of people with disabilities need to be supported by the right solutions. One potential solution is the development of a self-service system that is friendly to the deaf. This study aims to develop a self-service system that is friendly to the deaf and helps in obtaining information and services independently. The results achieved in this study are in the application of hand signal detection using the Long Short-Term Memory method which can overcome the problem of long-distance dependency and improve performance in recognizing complex hand signal patterns. The hand signal recognition feature can be improved by overcoming the problem of long-distance dependency with a maximum user distance of 1.25 meters, the system can still recognize hand signals well. It is hoped that in the future, more in-depth studies can be carried out on long-distance dependency for variations of other hand signal recognition methods, so that people with disabilities can more easily use the self-service system.